Market Integration and Intra-Industry Trade: A Survey of the Recent Literature and Some Further Suggestions - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1984)
The purpose of this pages is to review the recent literature on Indra-industry trade and to add some further insights into the likely causes of a phenomenon that has attacted the attention of many economists during the past twenty years; indeed intra-industry trade has been viewed as the most striking fact of intra-EEC trade that has accompained the establishment of the EEC, even though intra-industry trade was apparently present befor that event to a different extent and can also be observed in trade statistics of nations belonging to non-intefrated areas.
Keywords: 330